Edukasi gizi dengan nutricard-vidbook tentang zat gizi makro dan mikro serta cairan - Jasmine Raihana; Ditia Fitri Arinda; Indah Purnama Sari (Jurnal SAGO Gizi dan Kesehatan, 2024)
Background: Indonesia's sports achievements are still less impressive at the national, regional, and international levels. Sports performance in Indonesia is hindered and tends to decline, especially in events like the SEA Games, Asian Games, and the Olympics.Objective: To determine the impact of nutrition education through the media of nurticards and vidbooks regarding macro and micro nutrients, as well as fluids, on handball athletes in Palembang City.Methods: The research design is a quasi-experimental design with a sample size of 55 handball athletes in Palembang City, using total sampling as the sampling technique. Data collection was carried out through the completion of informed consent forms and questionnaires, as well as secondary data obtained from the sports branch authorities. Data analysis was performed using the Wilcoxon statistical test on the variables of knowledge and attitude. To identify differences in the average scores of knowledge and attitude between the two groups, the Mann-Whitney test was used.Results: The average knowledge and attitudes related to macro and micro nutrients and fluids among handball athletes in Palembang City improved before and after the education. In the knowledge variable, the intervention group had an average score of 10.04, while the control group scored 8.78. In the attitude variable, the intervention group had an average score of 44.25, whereas the control group scored 41.25. There was a significant impact of nutrition education through nurticards and vidbooks on the macro and micro nutrients and fluids knowledge among handball athletes in Palembang City (p < 0.05).Conclusion: There is an impact of nutrition education through nutricards and vidbooks on the knowledge and attitudes of handball athletes in Palembang City regarding macro and micro nutrients and fluids.